Effect of leadership style, work environment and financial compensation on employee performance (study at PT Bank X area, South Jakarta) - Aziz Setyawan; Wasi Bagasworo (Indonesia Banking School, 2018)
Indonesian banking conditions are currently growing rapidly, in line with the development of the Indonesian economy and era. This is reflected by the level of profit which is quite good in line withthe improving level of banking efficiency and strong banking capital. This study aims to analyze the performance of permanent employees at Bank X Area South Jakarta. This study uses variables of leadership style, work environment, and financial compensation to analyze the effect on employee performance. Data collection method used in this research is primary data by distributing questionnaire to Bank X Area South Jakarta permanent employee. Data collected by 100 respondents by using the Structural Equation Modeling (SEM) analysis. The summary of the result from this research are: 1) Leadership Style does not have a positive and significant influence on employee performance, 2) Work Environment has a negative effect on employee performance, 3) Financial Compensation have a positive and significant effect on employee performance at PT Bank X Area South Jakarta.